Tourism Destination Development Strategy Central Aceh - Syaripuddin, Syaripuddin (CV. Inara, 2021)
This paper discusses the Tourism Destination Development Strategy. In improving the tourism sector in an area, at least one has to develop the 3A concept (Attractions, Accessibility, and Amenities). The tourism sector is a mainstay for Central Aceh to be developed as a tourism destination because Central Aceh has attractions that can be developed into tourist attractions. The method used in this study using the Analytic Network Process (ANP) approach with the help of Super Decision software, by performing a synthesis analysis of problems, solutions, and strategies. The results of the respondents' answers indicated that the priority problems were infrastructure, attractiveness, and promotion problems. Meanwhile, the most priority solutions are solutions to improve infrastructure, namely transportation and travel, attraction, and promotion. And the most prioritized strategy is the improvement of infrastructure facilities and synergy.